THE MEANINGS OF THE DEVELOPMENT OF ALTERNATIVE TOURISM AT JASRI VILLAGE, SUBAGAN SUB-DISTRICT, KARANGASEM - Amerta, I Made Suniastha; Mudana, I Gede (E-Journal of Cultural Studies, 2017)
The alternative tourism developed in the form of a tourist village at Jasri Traditional Village is intended to empower and give opportunity to the local people to manage tourism at the village where they live. This is in accordance with the concepts of the community-based tourism development and sustainable development. This present study is aimed at knowing the meanings appearing from the development of the alternative tourism at Jasri Traditional Village. The qualitative method with the paradigm of cultural studies was used. Three theories which were eclectically used were employed to analyze the problems of the study. They are the theory of hegemony, the theory of power/knowledge, and the theory of communicative action.             The result of the study shows that the meanings appearing from the development of the alternative tourism at Jasri Traditional Village include the hegemonic meaning, the meaning of the economic potential empowerment, and the meaning of the socio-cultural sustainability. The hegemonic meaning includes (a) the implementation of the Regional Regulation ‘Perda’ Number 2 of 2002; (b) the implementation of the Regent’s Decree Number 658 of 2014; and (c) the meaning of image. The meaning of the empowerment of economic potential includes (a) the empowerment of the job opportunity potential; (b) the empowerment of the local people’s income potential; (c) the availability of the funds needed for funding the development at Jasri Traditional Village. The meaning of the socio-cultural sustainability made up of (1) the social sustainability including (1) the local people’s identity strengthening, (b) the better pride of becoming a community, (c) equality and justness in gender and age group;  and the meaning of cultural sustainability including (a) being aware of cultural conservation, (b) development of cultural value, and (c) cultural appreciation.